Influence of the diet on the bioaccumulation of heavy metals in small burrowing petrels from the Kerguelen Islands - Bocher, Pierrick; Caurant, Florence; Miramand, Pierre; Cherel, Yves; Bustamante, Paco (Polar Biology, 2003)
International audience Concentrations of cadmium, mercury, copper and zinc were measured in liver, muscle, kidney and stomach contents and the preys of five species of small burrowing petrels : South Georgian (Pelecanoides georgicus) and common (P. urinatrix) diving petrels, thin-billed (Pachyptila belcheri) and Antarctic (P. desolata) prions, and blue petrel (Halobaena caerulea). Inter-specific differences were significant for zinc concentrations in liver and kidney and for copper concentrations in the muscle. Blue petrel exhibited the highest mercury concentrations in the liver, but no significant difference were found for cadmium. Since they are very closely related species, concerning moult schedule, body size and life span (at least for four of them), their diet has been considered in order to evaluate its influence on heavy metal bioaccumulation. Both instantaneous exposure (with stomach content concentrations) and long term exposure –by the heavy metals analysis in the most frequent preys of their diet- have been evaluated. The most evident result is the influence of fish in the diet on the mercury levels. Diet does not seem to be discriminant for cadmium concentrations in the seabirds.